Exploring career advancement opportunities among women leaders at private sector - Nur Azreen, binti Ab Hadi (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study aims to explore the career advancement opportunities among women leaders in public sector in Malaysian perspective. Women also can achieve career advancement if they be treated fairly. Three research questions were outline based on the objectives and researcher has come out with five questions as the interview guire for data collection through semi-structured interview. Four informants were purposely chosen to fit the criteria as a women leader in private sector. The study was conducted using qualitative research design where the informants' understanding and perspectives about career advancement opportunities among women leader in Malaysia were gathered. The women leaders that had been interviewed in the public sector mostly well aware of career advancement. This study has provided the barriers and strategies that informants use to achieve career advancement. Generally, future research need to be done to construct a proper research for the career advancement opportunities in Malaysian perspective.